What are the Key Considerations to emerge from Information Technology Outsourcing Literature and how should Outsourcing Suppliers leverage these to improve their Market Position - Jones, J (2012)
The report provides the reader with the opportunity to firstly understand current Information Technology Outsourcing (ITO) literature and then secondly interpret it from the view point of a particular industry perspective: The Electronic Payment Industry. The ideal report output was that the author and subsequently readers of the report would be in a position to engage more effectively with potential industry customers and not only improve the chance of winning more business within the market place but more importantly, through more effective dialogue and understanding of the key considerations, ensure more effective solutions were delivered for any such customers. What has actually been delivered within the report can be categorised into two elements thus; a. Real actionable opportunities to improve engagement with new clients.